A case of bidirectional conduction block within the superior vena cava induced by cryoballoon pulmonary vein isolation. Issue 1 (3rd October 2018) - Watanabe, Tomonori; Hachiya, Hitoshi; Igarashi, Miyako; Kusa, Shigeki; Iesaka, Yoshito
Abstract: A 53‐year‐old male underwent a pulmonary vein isolation (PVI) of atrial fibrillation (AF) with a second‐generation cryoballoon (CB). Although the patient maintained sinus rhythm after the PVI, a superior vena cava (SVC) fibrillation was recorded by a circular‐multipolar‐electrode catheter positioned inside the SVC that suggested conduction block between the right atrium (RA)‐SVC connection. An adenosine triphosphate intravenous injection induced a dormant reconnection of the SVC myocardial sleeve and converted sinus rhythm to an AF rhythm. This case demonstrated that a CB application for the isolation of a right superior pulmonary vein could induce an electrical conduction block between the RA‐SVC connection.